Beseda o maloletnikh pravonarushiteliakh . Beseda o maloletnikh pravonarushiteliakh . Conversation about Juvenile Criminals . Беседа о малолетних правонарушителях - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Program discussing juvenile crimes. Featured in the program: Kirillov, Sergei Ivanovich (Minister of Internal Affairs of the Tatar S.S.R.); Slepnev, IU.V. (Head of the Criminal Investigation Department) Брифинг о состоянии молодежной преступности. В программе участвуют: Кириллов, Сергей Иванович (Министр внутренних дел Татарской ССР); Слепнев, Ю.В. (Начальник управления уголовным розыском)